Integrating Preclinical and Clinical Models of Negative Urgency - Halcomb, Meredith; Argyriou, Evangelia; Cyders, Melissa A. (Frontiers in Psychiatry, 2019)
Overwhelming evidence suggests that negative urgency is robustly associated with rash, ill-advised, behavior and this trait may hamper attempts to treat patients with substance use disorder. Research applying negative urgency to clinical treatment settings has been limited. We propose that the development of a viable, translational model of negative urgency is imperative for greater understanding of the neural correlates underlying this interaction and how best to intervene on negative urgency. To date, the literature implementing this type of model is sparse we believe, in part, due to the absence of an objective, behavioral, and translational model of negative urgency. We suggest that development of this model will allow for determination of prime neurological and physiological treatment targets, the testing of treatment effectiveness in the preclinical and the clinical laboratory, and, ultimately, improvement in negative urgency- related treatment response and effectiveness. In the current paper, we first review the literature on measurement of negative urgency and discuss limitations of current attempts to assess this trait in human models. Then, we review the limited research on animal models of negative urgency and make suggestions for some promising models and aspects to include in this work. Finally, we summarize the importance of translational models in the application of negative urgency to human treatment development and testing and make suggestions on necessary future work in this field. We suggest that future studies should seek to devise a translational model of negative urgency that is easily administered in both animals and human subjects. Given that negative urgency is a transdiagnostic risk factor that impedes treatment success, the impact of this work could be large in reducing client suffering and societal costs.